Antiviral effects of Shuanghuanglian injection powder against influenza A virus H5N1 in vitro and in vivo. (August 2018) - Tang, Yuling; Wang, Zhaohua; Huo, Caiyun; Guo, Xiaotong; Yang, Guanghui; Wang, Ming; Tian, Haiyan; Hu, Yanxin; Dong, Hong
Abstract: The current study was to identify a protective role of Shuanghuanglian (SHL) injection powder in vitro and in vivo after H5N1 viral infection. Immunofluorescent staining was used to determine the susceptibility of rat intestinal mucosa microvascular endothelial cells (RIM-MVECs) to the H5N1 virus. Viral replication of RIM-MVECs was measured by transmission electron microscopy (TEM) a hemagglutination assay and real-time quantitative PCR. H5N1 virally infected RIM-MVECs, and BALB/c mice were treated with SHL to investigate its therapeutic effect. Animal survival and the weight of H5N1 virally infected BALB/c mice after SHL treatment was noted, and histology and real-time PCR applied to mouse lungs were used to confirm the anti-H5N1 viral effects of SHL. RIM-MVECs supported replication of the H5N1 virus in vitro . SHL treatment reduced viral titers in H5N1 virally infected RIM-MVECs and mouse lungs. SHL -treated mice survived compared to controls. Mild pathological changes, reduced inflammatory cell infiltration and fewer viral antigens were observed in the lungs of SHL-treated mice at days 3 and 6 post-infection. In conclusion, SHL may have the antiviral activity against the H5N1 virus infection by inhibiting viral replication and alleviating lung injury. Highlights: Rat intestinal mucosa microvascular endothelial cells (RIM-MVECs) supported replication of the H5N1 virus in vitro . Shuanghuanglian (SHL) treatment reduced viral titers in H5N1 virally infected RIM-MVECs. SHL-treated mice displayed mild clinical manifestations and high survival rates when infected with IAV. SHL treatment induced milder pathological damage to lungs of IAV infected mice. SHL treatment caused reduced inflammatory cell infiltration and fewer viral antigens to lungs of IAV infected mice.